Epidemiologia molecular de Staphylococcus aureus em pacientes internados em hospital psiquiátrico e dependentes químicos atendidos em serviço hospitalar de referência no município de Botucatu, SP - Silvestre, Maíris Alarcão Duarte de Oliveira [UNESP] (2017)
Illicit drug users (IDUs) are recognized as a group at particular risk for staphylococci. In this population the first outbreak of community-associated Staphylococcus aureus (CAMRSA) was described. However, most studies relating S. aureus and MRSA to drug abuse address users of intravenous substances. In Brazil, most dependents are users of inhaled drugs, especially crack. A proportion of these IDUs have multiple passages through recovery clinics. Another institutionalized group still relevant in Brazil are patients with long-term hospitalizations in psychiatric hospitals. In spite of the psychiatric reform and its emphasis on deinstitutionalization, aspects of social vulnerability and abandonment by relatives also determine the residence of patients in psychiatric hospitals. The two groups described above are exposed to different epidemiological pressures and are both at higher risk of invasive staphylococcal disease and in a strategic position for maintenance and dissemination of isolates. The objective of this study was to identify the prevalence and predictors of the carrying of S. aureus and MRSA in IDUs admitted to the Hospital of Reference for Alcohol and Drugs (SARAD) and patients residing in the Psychiatric Hospital Cantídio de Moura Campos, both located in Botucatu , São Paulo State, Brazil. Molecular characterization of MRSA isolates was performed. A total of 220 subjects were enrolled, 138 from the SARAD and 82 from the psychiatric hospital. The prevalences of S. aureus and MRSA for the two services were 26.8% / 4.5% and 24.3% / 7.3%, respectively. The use of inhaled cocaine was associated with increased carryiage of S. aureus among chemical dependents, while age was negatively associated with this outcome in the patients of the psychiatric hospital. Analysis of 14 MRSA isolates from 10 subjects revealed a cluster comprising 8 isolates from 5 subjects. Our findings suggest that the prevalence of MRSA colonization in the groups studied is higher than that found in the general population. These groups are therefore more vulnerable to difficult-to-treat infections and can contribute to the spread of MRSA in their social networks and in the population as a whole.